CNTs based lubricating oils for UAZ 31512 engines. (1st October 2016) - Hong, Nguyen Manh; Thang, Bui Hung; Hong, Phan Ngoc; Hong, Nguyen Tuan; Khoi, Phan Hong; Minh, Phan Ngoc
Abstract : The obtained results on application of the carbon nanotubes (CNTs) in lubricating oils for UAZ 31512 engine are presented. The calculation results showed that the thermal conductivity of lubricating oils increase about 10% when using lubricating oil with 0.12 vol% of CNTs concentration. The experimental results on Ulyanovskiy Avtomobilnyi Zavod 31512 (UAZ 31512) engine on pedestal at free load showed that the temperature of engine dropped about 10°C and the fuel saving was up to 10% when using lubricating oil with 0.12 vol% of CNTs concentration.